Ten-year 15 N labeling reveals the nitrogen retention threshold for maximizing carbon sequestration in a temperate forest - Bai Liu; Xianlei Fan; Ziping Liu; Qing Chang; Jiancheng Chen; Yingdong Huo; Edith Bai (Proceedings of the National Academy of Sciences, 2026)
Anthropogenic nitrogen (N) deposition comprising reduced (NH x ) and oxidized (NO y ) forms, differentially influences ecosystem processes. However, their long-term fates and collective impacts on ecosystem nitrogen use efficiency (NUE) and carbon (C) sequestration remain unresolved. Here, using a decade-long paired labeling ( 15 NH 4 + and 15 NO 3 − ) experiment in a temperate forest, we demonstrate that initially distinct fates of different N forms converged within 2 y due to low initial loss rates prior to organic incorporation. After 10 y, overall ecosystem retention was remarkably similar (55.3 to 65.6%) for both N forms. A process -based N-cycling model was built and parameterized by our 15 N recovery data and the model predicted declining ecosystem NUE with increasing N deposition level. We further identified a deposition-induced C sequestration potential of 41.41 kg C kg −1 N under an incremental deposition of 10 kg N ha −1 y −1 , exceeding prior estimates at comparable loads. This study provides mechanistic, high-resolution temporal data critical for refining N-cycle models and reveals an optimal N deposition range (20 to 30 kg N ha −1 y −1 ) that maximizes C sequestration while minimizing environmental risks (e.g., nutrient imbalance, eutrophication) in temperate forests.